Cost Minimization Analysis of Radiofrequency Compared to Laser Thermal Ablation in Patients with Hepatocellular Carcinoma - Maria Guarino; Lucia Sara D'Angiolella; Luigia Falco; Federica Morando; Giovan Giuseppe Di Costanzo; Filomena Morisco; Giovanni Improta; Lorenzo Giovanni Mantovani; Nicola Caporaso (Farmeconomia: Health Economics and Therapeutic Pathways, 2019)
BACKGROUND: Over the last decade of years, minimally invasive techniques have been developed for the treatment of hepatocellular carcinoma and liver metastases. We sought to investigate the health costs associated with the management of patients with hepatocellular carcinoma treated with radiofrequency vs laser thermal ablation and their clinical outcomes. METHODS: We performed a retrospective analysis of the ablations performed in two referral centers in southern Italy, from 2009 to 2013. Resource use was valued by year 2017 official prices, in €. Direct healthcare costs (drugs, visits, tests and hospitalizations) of different ablation techniques were compared. Total costs were analyzed from Italian NHS perspective. RESULTS: A total of 140 patients were identified. Baseline demographics and clinical outcomes of interest did not differ between the two groups. Patients treated with laser thermal ablation resulted in an expected annually cost savings of 258.9 € per patient, in one-year follow-up healthcare costs compared with radiofrequency. The largest components of annual medical expenditures were attributable to drugs, regardless of the type of ablative technique. CONCLUSIONS: The ablation using either laser thermal ablation or radiofrequency is equally effective. Laser thermal ablation would carry disposable cost savings as compared to radiofrequency. The costs associated with management of patients with hepatocellular carcinoma, treated with laser thermal ablation were lower than those treated with radiofrequency ablation.